جدل الحداثة بين التأصيل والتجديد في الثقافة العربية عند طه عبد الرحمن - شقير, صالح; شلغين, عهد كمال (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
حاولت هذه الدراسة البحث في موقف طه عبد الرحمن، من الفكر العربي المعاصر، من حيث الكشف عن مدى تطبيق وجديَّة مفهوم الحداثة فيه، فالحداثة في الثقافة العربية تتنازعها عدة اتجاهات فكرية مختلفة في رؤاها، ولما كان التراث يمثل الأصالة، فإن كيفية المحافظة عليها من أولويات البحث في الحداثة. إلاَّ أن طه عبد الرحمن يرفض مقولات الحداثة الغربية ويعتبرها آفة على الفكر العربي وتراثه، مما دفع به إلى بناء مشروع فكري أساسه الإبداع داخل الثقافة العربية الإسلامية، منطلقاً من فكرة المجال التداولي العربي، ليصل إلى نتائج وتعميمات مفادها أن الحداثة لا تقوم إلا من خلال تأصيل الجانب الفقهي في الثقافة العربية. ويظهِر البحث في هذا السياق أنه لا يمكن قبول هذه النتائج والتعميمات، نظراً لأن طه عبد الرحمن قد استند إلى مجال ضيق شمل به كل التراث العربي، ونظر إلى في الثقافة العربية على أنها ثقافة مقلِّدة الأمر الذي يفرغها من أي هُويَّة فكرية وحضارية عبر تاريخها الطويل.This study tried to examine Taha Abdul-Rahman’s position towards thecontemporary Arab Thought in terms of detecting the extent of seriousness of the application of the modernity concept. Modernity in the Arab culture was stuck between several different ideological trends since the heritage of originality representsmaintaining of priorities for research in modernity. However, Taha Abdul-Rahman refuses arguments of Western modernityas a lesion to the Arab Thought and heritage, prompting him to build an intellectual project based on innovation within the Arab-Islamic culture. The starting point was the idea of the Arab deliberative field. To hit conclusions, suchresults and generalizations cannot be reliable since it only included rooting idiosyncratic side of the Arab culture. The research shows within this context that itcannot accept these results and generalizations because Taha Abdul-Rahman based on the primitive field which did not cover allthe areas of the Arabic heritage.